IMPLEMENTASI BUMN CORPORATE SOSIAL RESPONSIBILITY DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Made Widani (Jurnal Ilmiah Satyagraha, 2023)
In the situation of the Covid-19 Pandemic that is still engulfing theworld, especially in Bali, it is not only the tourism sector that is affected, but alsoall industries in Indonesia, both the private and government sectors. In this case,the SOEs also feel the impact of the virus that has ravaged the world economy.However, SOEs are still intent on carrying out a caring program in improving thewelfare of the community in the form of implementing Corporate SocialResponsibility which is a commitment by BUMN companies to improve thewelfare of the community, especially in the province of Bali and is also a form ofgovernment concern that is carried out through BUMN companies in distributingfunds and assistance both physically and mentally. material and non-material tothe community to improve and help economic problems.